The Influence of College Students’ Perception of Green Inclusive Leadership on Green Creativity: The Mediating Role of Green Intrinsic Motivation - Liu, Jia-Xin; Huang, Jian-Hao (Journal of Ecohumanism, 2024)
Green creativity among college students is essential for achieving sustainable development goals. Leadership significantly influences the cultivation and enhancement of students’ creative abilities. Grounded in Self-determination theory, this study developed and tested a research model to examine the mediating role of students’ green intrinsic motivation. Data were collected from 598 college students in Hebei Province, China, and analyzed using SPSS. The results show that students’ perceptions of green inclusive leadership positively affect green creativity, with green intrinsic motivation serving as a mediating factor. This research advances the knowledge domain regarding green inclusive leadership and green creativity.